2016
DOI: 10.1039/c5ra23148e
|View full text |Cite
|
Sign up to set email alerts
|

Phthalazinone structure-based covalent triazine frameworks and their gas adsorption and separation properties

Abstract: In this work, new classes of phthalazinone-based covalent triazine frameworks (PHCTFs) were prepared by ionothermal synthesis from two full rigid dicyano building blocks with rigid, thermostable and asymmetric N-heterocycle-containing structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 91 publications
1
35
0
Order By: Relevance
“…Only in the past few years, several attempts to generate triazine-based microporous polymer materials for gas sorption processes were realized [ 14 18 ]. A microporous structure with major pore size around 1 nm was found in either hybrid or pure CER networks synthesized without implication of any porogen, i.e., due to intrinsic microporosity representing free volume (voids) arising from the formation of triazine-based macrocycles in a rigid network structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only in the past few years, several attempts to generate triazine-based microporous polymer materials for gas sorption processes were realized [ 14 18 ]. A microporous structure with major pore size around 1 nm was found in either hybrid or pure CER networks synthesized without implication of any porogen, i.e., due to intrinsic microporosity representing free volume (voids) arising from the formation of triazine-based macrocycles in a rigid network structure.…”
Section: Introductionmentioning
confidence: 99%
“…The materials obtained have shown high gas adsorption capacities (H 2 , CO 2 , N 2 ) with good selectivities for several gas pairs, namely CO 2 /N 2 , CO 2 /CH 4 , etc. [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional, the narrow pore size distribution also leads to ne selectivity. 39 Although MOP-Ad-1 showed the highest CO 2 uptake, lower selectivity was obtained due to a higher content of mesoporous surface area and wider pore size distribution in the structure, which apperas to be disadvantageous for the recognition of small CO 2 molecules (3.30 A) over the large CH 4 (3.82Å) molecule. Additionally, it was found that the three MOP-Ad networks exhibited a slightly lower CO 2 /CH 4 selectivity than some functionalized 3D microporous organic polymers, such as tetraphenylethylene-based microporous organic polymers (MTPOPs, 5.4-7.2 at 273 K), 9 and tetraphenyladamantane-based microporous polybenzimidazoles (PBI-Ads, 9.0-11.0 at 273 K), 35 N-doped porous carbons (NAHA, 7.9-10.7 at 273 K), 40 benzothiazole-and benzoxazole-linked porous polymers (6.9-9.4 at 273 K), 38 and the mesoporous polymeric organic frameworks (mesoPOF, 10-15 at 273 K).…”
Section: Characterization Of Mop-ad Networkmentioning
confidence: 97%
“…Several methods have been developed for the synthesis of CTFs, which are ionothermal synthesis [6], superacid catalysis [10], transition metal coupling reactions [11], and polycondensation method [12]. CTFs are reported to be practicable in a number of functional applications, such as gas adsorption and storage [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29], heterogeneous catalysis [14,30,31,32,33,34,35,36,37,38,39,40,41,42,43], energy storage and conversion [44,45,46,47], photocatalysis [12,48,49,50,51,52]. In this review, we selected typical examples of CTFs reported in the literature and reviewed the recent development in their synthesis and application in gas adsorption and catalysis in relation to energy and environment issues.…”
Section: Introductionmentioning
confidence: 99%